Rancang Bangun Aplikasi Pembelajaran Bahasa Korea Kelas X Berbasis WEB (STUDI KASUS: SMA Barunawati Surabaya) - Fadila, Rullyana Nur; Hariadi, Bambang; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
The korean language used as a subject in the level of education high school. The korean language used as a subject nuclei at high school curriculum especially in high school barunawati surabaya class x. Learning the korean language in high school barunawati use book as the tools learning , but as time passes a book regarded less attractive to students .In addition , the students find it difficult to reach standart ketuntasan the value of ( skn ) subjects especially language korea .Based on the background mentioned above , writer design wake up application learning the korean language. With the this application , teachers can give the subject matter and exercises ( quiz) for students at the time outside the school. Application report the quiz to evaluation teachers at the school. In addition , by using this application , students able to read or download the subject matter given by teachers in anywhere and anytime , so that the student learning not only happened in school .In this application system can help the teacher and students to better understand the korean language. A system used to a person or high school students barunawati class x can run well and can help the learning the korean language. Teachers can give matter and training to students to practice outside the school. To advise development application learning is expected to connected with information system academic school as input value exercise or the examination.